The Environment and Sustainable Local Development in Coastal Areas - Lourenço, Nelson (2012)
Between 1998 and 2002 a multi-national research project – Measuring, monitoring and managing sustainability: the coastal dimension – was funded by the International Cooperation with Developing Countries programme of the European Commission. The project analysed interactions between social and environmental issues to better understand the impact of socio-economic drivers on ecosystems, focusing on issues of importance to sustainable coastal development planning and management. This included a consideration of stakeholder sensitive instruments to support coastal policy-making.